Prospects for the use of plant analogue of myoglobin in plant-based meat product - Fursik, Oksana; Strashynskyi, Igor; Pasichnyi, Vasyl (My University, 2022)
In order to ensure mass transition of the population to the consumption of plant analogues of meat products, their organoleptic properties need to be improved. Therefore, it is important to search for substances which can reproduce the organoleptic characteristics of the meat product, especially indicators of appearance and taste.
Keywords: кафедра технології м’яса і м’ясних продуктів; myoglobin; plant-based mat producer; organoleptic characteristics